A importância do enriquecimento ambiental para o desenvolvimento motor de bebês - (:unkn) unknown (Universidade Federal do Pampa, 2022)
Motor development is the evolution of motor skills resulting from the influence of biological and environmental processes. Preterm babies tend to present a greater probability of deviations in their motor performance, demanding ample stimulation. This cross-sectional, descriptive and comparative study aimed to analyze the opportunities for environmental enrichment and the motor development of babies living in Uruguaiana, RS. The Affordances in the Home Environment for Motor Development - Infant Scale (AHEMD-IS) and Alberta Infant Motor Scale (AIMS) instruments were used to assess home opportunities and motor development, respectively. The sample consisted of 59 babies, 22 of which were premature. The results showed that a higher percentage of full-term babies had delayed motor development compared to preterm infants, who mostly attend the Clinic for Risk Babies (CRB). In environmental opportunities, 15,3% of the households had an excellent score and 45,87 % less than adequate, and the percentage of homes where the environment is excellent and adequate is higher in those who attend the CRB. There was a significant difference in favor of the group that attended the Risk Clinic in terms of the amount of physical space, the variety of stimuli and the total AHEMD-IS result. The data indicate that early stimulation programs, with Family participation in the construction of a home environment rich in stimuli, positively impact motor development, preventing or attenuating possible motor delays in premature infants.
The importance of environmental enrichment for motor development of babies
Keywords: Motor development; Preterm babies; Stimulation programs; Desenvolvimento motor; Práticas maternas; Programas de estimulação; CNPQ::CIENCIAS DA SAUDE